Orally Induced Fibrinolysis. A Critical Assessment of Pineapple Protease - Hawkey, Christine; Howell, Margaret (Thrombosis and Haemostasis, 1964)
1. An enzyme Bromelain derived from the stalk of the Hawaiian pineapple has been studied. It is shown to be proteolytic in vitro against casein and fibrin, the effect on fibrin being direct and not due to activation of the fibrinolytic system.2. The enzyme is not inhibited by the antiplasmins present in human serum.3. The enzyme has in vitro antithrombin activity.4. Oral doses of up to 5 mg/Kg body weight of enteric coated capsules of the enzyme failed to produce any detectable proteolytic activity in the plasma of human recipients. A possible explanation for this is offered.